Applications of Design for Manufacturing and Assembly - Păcurar, Ancuţa (IntechOpen, 2019)
The book entitled Application of Design for Manufacturing and Assembly aims to present applicable research in the field of design, manufacturing, and assembly realized by researchers affiliated to well-known institutes. The book has a profound interdisciplinary character and is addressed to researchers, engineers, PhD students, graduate and undergraduate students, teachers, and other readers interested in assembly applications. I am confident that readers will find interesting information and challenging topics of high academic and scientific level within this book. The book presents case studies focused on new design for special parts using the principles of Design for Manufacturing and Assembly (DFMA), strategies that minimize the defects in design and manufacturing applications, special devices produced to replace human activity, multiple criteria analysis to evaluate engineering solutions, and the advantages of using the additive manufacturing technology to design the next generation of complex parts, in different engineering fields.